In vitro and in vivo evaluation of alginate hydrogel-based wound dressing loaded with green chemistry cerium oxide nanoparticles - Zhao, Ran; Zhao, Chenyuyao; Wan, Yi; Majid, Muhammad; Abbas, Syed Qamar; Wang, Yibing (Frontiers in Chemistry, 2023)
Interactive wound dressings have displayed promising outcomes in enhancing the wound healing process. This study focuses on creating a nanocomposite wound dressing with interactive and bioactive properties, showcasing potent antioxidant effects. To achieve this, we developed cerium oxide nanoparticles utilizing curcumin as both the reducing and capping agent. Characterization techniques such as SEM, EDX, DLS, Zetasizer, FTIR, and XRD were utilized to analyze the cerium oxide nanoparticles synthesized through a green approach. The image analysis on the obtained TEM images showed that the curcumin-assisted biosynthesized CeO2NPs have a size of 18.8 ± 4.1 nm. The peaks located at 28.1, 32.7, 47.1, 56.0, 58.7, 69.0, and 76.4 correspond to (111), (200), (220), (311), (222), (400), and (331) crystallographic planes. We applied the Debye–Scherrer equation and observed that the approximate crystallite size of the biosynthesized NPs is around 8.2 nm based on the most intensive broad Bragg peak at 28.1°. The cerium oxide nanoparticles synthesized were integrated into an alginate hydrogel matrix, and the microstructure, porosity, and swelling behavior of the resulting wound dressing were assessed. The characterization analyses provided insights into the physical and chemical properties of the green-synthesized cerium oxide nanoparticles and the alginate hydrogel-based wound dressing. In vitro studies demonstrated that the wound dressing based on alginate hydrogel exhibited favorable antioxidant properties and displayed hemocompatibility and biocompatibility. Animal studies conducted on a rat full-thickness skin wound model showed that the alginate hydrogel-based wound dressing effectively accelerated the wound healing process. Overall, these findings suggest that the alginate hydrogel-based wound dressing holds promise as a highly effective material for wound healing applications.